Opioid overdose crises during the COVID-19 pandemic: implication of health disparities - Ishika Patel; Lauren A. Walter; Li Li (BMC, 2021)
Abstract Background Recent data suggest a disproportionate impact of opioid overdoses on Black Americans. The study aims to describe emergency department (ED) visits at a Southern, urban ED pertaining to opioid overdose and associated health disparities. Methods Patients presenting to the ED at the University of Alabama at Birmingham Hospital with opioid overdoses from January 1 to October 31, 2019, and from January 1 to October 31, 2020, were identified from electronic medical records. Results The total number of opioid overdose visits increased 9.7% (556 to 611) between January and October 2020 compared with 2019. Among patients who presented with opioid overdose, the mean ages were 50.3 years and 48.3 years, in 2019 and 2020, respectively. In both 2019 and 2020, more Blacks than whites were treated for opioid overdose in the ED (284 vs. 258 in 2019, and 306 vs. 271 in 2020) although 28 patients did not record their race in 2020. Consistently, more overdose deaths were observed in Blacks than in whites in 2020. More individuals seeking opioid overdose treatment were single in both years. Conclusions The study reported a greater number of visits for opioid overdoses from January to October of 2020 in an ED of a southeastern region, as well as higher overdose deaths in Blacks. Our findings highlight the importance of substance use treatment, harm reduction, and overdose prevention efforts that should be immediately present to reduce opioid overdose, especially for vulnerable populations in the South, i.e., Black community, and individuals experiencing singlehood.